Effect of activated carbon obtained from vinasse and marc on the rheological and mechanical characteristics of the bitumen binders and hot mix asphalts - Seyrek, Elif Seyma; Yalcin, Erkut; Yilmaz, Mehmet; Kok, Baha Vural; Arslanoglu, Hasan (Elsevier Sci Ltd, 2020)
This study examined the effect of the activated carbon, obtained from marc and vinasse agricultural wastes and used in the bitumen modification, on the rheological characteristics of bitumen binders and mechanical properties of hot mix asphalt. For this purpose, the activated carbon, obtained from vinasse generated at distillation step in the alcohol production from molasses together with grape marc, was used. The activated carbon was added to neat bitumen (PG 58-16) in 3 different ratios (5%, 10%, and 15% by weight of neat binder). The following tests were applied to the neat and modified bitumen: BBR (bending beam rheometer), DSR (dynamic shear rheometer), rotational viscosity, softening point, and penetration. The HMA samples were prepared using the neat and modified binders. The following tests were applied to the HMA samples: Marshall stability and flow, resistance against the damage induced by moisture, indirect tensile stiffness modulus, cyclic creep, and indirect tensile fatigue. Considering the binder test results, it was determined that using the activated carbon in the bituminous modification increased the stiffness and high-temperature performance of the bituminous binders, while the lowtemperature performance was not affected much. Based on the mixture tests, it was found that using the activated carbon modified bitumen increased the Marshall stability, stiffness, resistance against the fatigue cracking, and permanent deformation of mixes. On the other hand, the use of activated carbon in bitumen modification adversely affected the resistance against the moisture-induced damage. (C) 2019 Elsevier Ltd. All rights reserved.
Keywords: Activated carbon; Bitumen modification; Vinasse; Marc; Asphalt performance